2000
DOI: 10.1073/pnas.97.3.1299
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant development of motor axons and neuromuscular synapses in erbB2-deficient mice

Abstract: Receptor tyrosine kinase erbB2, which is activated by neuregulin, is expressed in Schwann and muscle cells in the developing neuromuscular junction (NMJ). In vitro studies have shown that neuregulin promotes the survival and migration of Schwann cells and stimulates acetylcholine receptor gene transcription in cultured muscle cells. These findings suggest an important role for erbB2 in the development of the NMJ. Here we examine erbB2-deficient mice to determine whether erbB2 is required for NMJ development in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
116
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(123 citation statements)
references
References 35 publications
5
116
1
1
Order By: Relevance
“…This is the stage at which the developing phrenic nerve first arrives at the diaphragm muscle and is before the clustering of muscle AChRs (Lupa and Hall, 1989;Lin et al, 2000). Our results showed that motor nerves exit the spinal cord normally and remain fasciculated en route to their muscle target in the Chat mutant embryos (data not shown).…”
Section: Increased Innervation and Spinal Motor Neuron Survivalsupporting
confidence: 48%
“…This is the stage at which the developing phrenic nerve first arrives at the diaphragm muscle and is before the clustering of muscle AChRs (Lupa and Hall, 1989;Lin et al, 2000). Our results showed that motor nerves exit the spinal cord normally and remain fasciculated en route to their muscle target in the Chat mutant embryos (data not shown).…”
Section: Increased Innervation and Spinal Motor Neuron Survivalsupporting
confidence: 48%
“…In addition, mice deficient in ErbB2 show defects in cranial sensory ganglia likely due to defects in cranial neural crest [119,123]. ErbB2 plays a role in the terminal differentiation of oligodendrocyte precursors to mature oligodendrocytes in the spinal cord [124] as well as in the myelination of peripheral nerves by Schwann cells [125][126][127]. Rescue of the embryonic lethal cardiac defects of ErbB2-deficient mice by myocardium-restricted expression of wild-type ErbB2 results in mice with severe defects in Schwann cell migration in the peripheral nervous system with loss of sensory and motor neurons [125,126].…”
Section: Erbb Members In Mammalian Developmentmentioning
confidence: 99%
“…Neuregulin-1 is expressed in the endocardium and appears to act in a paracrine fashion through myocardium-restricted ErbB2 and ErbB4 to stimulate myocardial trabeculae formation [129,137]. Neuregulin-1-deficient mice also have deficient Schwann cell and cranial ganglia formation similar to those seen in ErbB2 and ErbB3 mutant mice [120,[125][126][127][128]137]. Similarly, deletion of HB-EGF, a ligand for both EGFR and ErbB4, leads to dilated cardiomyopathy similar to conditional mutant mice lacking ErbB2 or ErbB4 in the ventricular myocardium [138].…”
Section: Erbb Members In Mammalian Developmentmentioning
confidence: 99%
“…NRG binds to ErbB receptors and, through the initiation of Erk signaling pathway, induces the transcription of synapse-specific genes, such as AChR subunits (13). Nonetheless, recent studies indicate that, although conditional mutant mice lacking NRG or ErbB receptors exhibit neuromuscular defects, the pattern of AChR transcription remains grossly normal in these mice (14)(15)(16).…”
mentioning
confidence: 99%